Brushstrokes and Billions: Unveiling the Evolving Landscape of China’s Art Auction Market, 2012 to 2019 - To-Han Chang; Chiung-Yu Huang (SAGE Open)
This investigation employs quantile hedonic regression methodology to analyze China’s painting and calligraphy auction market during the critical 2012 to 2019 adjustment and maturation period. Utilizing a comprehensive dataset of 47,540 artworks, we examine how artist reputation, artwork characteristics, and sale attributes influence valuation across different price segments. Our findings reveal substantial heterogeneity in the implicit prices of these attributes throughout the price distribution, providing empirical validation for market segmentation hypotheses previously unexplored in the Chinese context. Quality-adjusted price indices demonstrate a general downward trajectory, most pronounced in premium market segments following 2012, possibly influenced by political factors. Notably, we document a convergence phenomenon in price indices across market segments toward the study period’s conclusion, suggesting progressive market maturation—an observation corroborated by industry specialists. These findings substantively advance theoretical frameworks of art valuation while offering strategic insights for market participants navigating this complex marketplace.